Penetrating cardio-thoracic injuries at a district level hospital in Cape Town South Africa : A retrospective case audit - Hameed-Ikram, Sarwat (Department of Anaesthesia, 2018)
The Khayelitsha District Hospital (KDH) faces the difficult challenge of managing patients with high acuity penetrating cardiothoracic injuries, but without the full complement of resources to provide optimal care. At the time of this dissertation, we were unaware of the outcome of patients cared for at KDH, and of any potential modifiable risk factors that could improve their outcome. We therefore undertook a retrospective case audit to determine the outcome of patients presenting alive at our emergency unit with penetrating chest injuries (PCI). Objective: The objective of this study is to audit the KDH experience with penetrating chest injuries and to identify potential risk factors that predict outcomes in patients who sustain these injuries and require surgery at this district level hospital. The total study duration was 34 months. Methods: A retrospective review of all medical records of patients with PCI who were alive on presentation and had undergone surgery at KDH between 1st February 2012 and 31st December 2014 was undertaken .An audit was conducted on these files. During the audit, affected patient's clinical and physiological variables on admission, intra- and post-operative were collected and evaluated as potential predictors of outcome. This study also assessed a possible relationship between physiological parameters together with arterial blood gases (ABG) on presentation with immediate 48-hour mortality. The selected variables were: SBP (systolic blood pressure) <90 mmHg or >90 mmHg, palpable pulse, presence of a precordial stab wound, vascular injury, base deficit (BD) and lactate. A logistic regression analysis was performed to investigate the relationship between the selected variables and the 48-hour mortality. The relationship between fluid, BD and lactate was compared using Pearson correlation. Continuous data is presented as means ± standard deviations. Estimates for predictor variables are presented with odd's ratios (OR) and 95% confidence intervals (95% CI). Permission of this study was gained from human research ethics committee of University of Cape town. Results: Over the 34-month study period, a total of 646 patients were admitted to KDH with penetrating cardiothoracic trauma. Fifty-six patients required surgery at KDH. These results show that KDH had a PCI incidence of 5.1%, and that this was predominantly amongst males in the 15 - 24 year age group. Fifty-five patients were male and only one female. Of the 56 operated patients, 37 (66%) presented in hemorrhagic shock with SBP < 90mmHg. The mean amount of resuscitation fluid, which included both crystalloid and colloid, administered in the Emergency Room (ER) was 2481 ml per patient. Ten (17.8%) patients had a front room thoracotomy (FRT), with a mortality rate of 6 (60%). The overall mortality rate amongst operated patients was 16 (31.3%). Thirty-three patients (58.9%) had an isolated cardiac chamber injury and 23 (41.1%) had a vascular injury. Mortality amongst patients with isolated cardiac chamber injury was 5 (31.2%) and mortality among patients with isolated vascular injury was 7 (43.7%). Two patients sustained a combined cardiac and vascular injury with a mortality of 12.5%. The results of the logistic regression analysis revealed no statistically significant correlation between the selected predictors and 48-hour mortality (p-values: BP<90mmH p=0.27, palpable pulse p=0.181, precordial stab p=1.17, vascular injury p=0.38, BE p=0.98, Lactate p=0.06). Additionally, there was no statistically significant relationship between administered EC fluids and the acid base severity (Pearson correlation coefficient: BD r =0.091, Lactate r = -0.13). Conclusion: Physiological (blood pressure, pulse) and ABG parameters (lactate and base deficit) were not identified as significant risk factors for survival in the sample studied. The risk factor of isolated cardiac injury carried a better prognosis. Logistic regression analysis did not support the initial observation of higher mortality in patients with vascular injury. Additionally, there was no correlation between the severity of the acid base disturbance and the volume of fluid administered during resuscitation in ER. The outcomes of patients with PCIs presenting at KDH was within those published in the literature (range of published mortality: 17%-80%, survival 3-84%). The ideal predictor for PCI outcome in our cohort was indeterminate. Limitations of this study that include a small sample size and incomplete medical records, may have led to a type 2 error. A more comprehensive prospective study with meticulous record keeping is required to identify the factors that can influence the outcome of patients with PCI.